Montreal’s Sanctuary Policy for Non-Status Migrants: Opportunity and Obstacles - Atak, Idil; Hudson, Graham (Refuge, 2022)
In February 2017, the city of Montreal adopted a policy entitled Access to Municipal Services Without Fear with a view to allowing non-status migrants to access some municipal programs and services without fear of being arrested and removed from Canada. This article offers a critical analysis of the city of Montreal’s policy. We discuss the main barriers to implementation, namely, the limited jurisdictional power and authority of the city in migration matters and the municipal police’s refusal to comply with the policy. We draw on the conceptual framework of the sanctuary city to argue that the municipality crafted creative solutions to barriers as part of its bid to make the city more inclusive.